The Influence of Service Quality, Facilities, and Location on Customer Satisfaction at Luceo Pool And Cafe, Malang - Evi Anggraini; Mohammad Bukhori; Sudjilah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Increasing competition in the pool-and-cafe industry requires businesses to identify the factors associated with customer satisfaction. This study examined the relationships between service quality, facilities, location, and customer satisfaction at Luceo Pool and Cafe in Malang, both individually and collectively. A quantitative research design was employed. The study population comprised 564 customers who visited the establishment between January and March 2026. A sample size of 86 respondents was calculated using the Slovin formula, and participants were selected through purposive sampling. Primary data were collected through an online questionnaire administered via Google Forms and analyzed using multiple linear regression in SPSS. Service quality did not significantly predict customer satisfaction (t = 1.676, p = 0.098), nor did facilities (t = 1.567, p = 0.121). In contrast, location was a positive and significant predictor of customer satisfaction (t = 4.179, p < 0.001). Collectively, service quality, facilities, and location significantly predicted customer satisfaction (F = 25.422, p < 0.001), explaining 48.2% of its variance (R² = 0.482). These findings identify location as the only significant independent predictor within the analyzed model, underscoring the importance of accessibility and visibility in shaping customer satisfaction. Nevertheless, the significant overall model indicates that customer experience should be managed comprehensively. Luceo should therefore preserve its locational advantages, improve parking convenience, and continuously maintain service quality and facilities.